The Global Pandemic as Learning Opportunities about the World: Extending School Curriculum - Bogum Yoon (Middle Grades Review, 2020)
The purpose of this essay is to offer middle grades educators with suggestions on promoting students’ global perspectives by using the international pandemic as a main topic during and after the COVID-19 crisis. The outbreak of the coronavirus has affected individuals’ lives and education around the world including the United States. This phenomenon invites educators to work with students for deepening their understanding about the interconnected world as global citizens. Yet, education about the world is severely lacking. There is little in-depth discussion on how educators can help young adolescents to learn this interconnected world concept by using the current reality in the middle grades field. Grounded in broader constructs of global, critical, and multicultural literacy, this essay provides specific instructional suggestions on how the global pandemic can be used as learning opportunities about the world as a way to extend school curriculum. The essay contributes to the middle grades field by offering new insights to educators who seek ways to engage young adolescents about the world through meaningful literacy activities across content areas.
Keywords: Global pandemic; world; global perspectives; literacy learning; middle school; pandemic pedagogy